Supplemental Protein and Multi-Nutrient Beverage Improve Skin Barrier Restoration of an Experimental Wound Site During 72-h Sleep Restriction. (29th May 2020) - Smith, Tracey; Wilson, Marques; Whitney, Claire; Fagnant, Heather; Karl, J Philip
Abstract: Objectives: Acute bouts of sleep restriction (SR) are unavoidable in certain populations (e.g., military personnel and first responders), and impairs immune function as evidenced by delays in skin barrier recovery of experimental wounds by ∼1 day. To what extent this impairment can be mitigated by nutritional supplementation is less clear. We tested the efficacy of a multi-nutrient beverage and additional protein on wound healing in response to acute SR. Methods: In this single-blind, cross-over study, wounds were created in healthy adults by removing the top layer of ≤ 8 forearm blisters (∼30 mm 2 ) induced via suction on Day 2 of 72-h SR (lab monitored, 2-h nightly sleep). A controlled, isocaloric diet was provided during SR with either 0.9 g · kg −1 · d −1 protein plus placebo (PLA) or 1.5 g · kg −1 · d −1 protein plus multi-nutrient beverage (NUT; L-arginine: 20 g · d −1, L-glutamine: 30 g · d −1, omega-3 fatty acids: 1 g · d −1, zinc sulfate: 24 mg · d −1, vitamin D3: 800 IU · d −1 and vitamin C: 400 mg · d −1 ). For 4 days following SR, participants were instructed to continue with the respective PLA or NUT treatment. Protein prescription and beverage components were based on data from clinical settings that have shown benefits related to postsurgical infectious complications and wound healing disorders. Skin barrier restoration was assessed by transepidermal water loss, measured daily until values were within 90% of unbroken skin. Results: Twenty participants completed PLA and NUT (18 M/2F; 19.7 ± 2.3 years [mean ± SD]), Body weight change was not different during PLA and NUT (–0.06 ± 0.88 kg and −0.12 ± 1.54 kg, respectively, P  = 0.90) and dietary protein intake during and after SR was 1.08 ± 0.28 g · kg −1 · d −1 and 1.44 ± 0.27 g · kg −1 · d −1, respectively. Compliance with study beverages was ∼95%. Skin barrier recovery time was shorter for NUT (4.29 ± 1.17 days) compared to PLA (5.48 ± 1.30 days) ( P  = 0.001). Conclusions: Supplemental nutrition may be beneficial for mitigating delays in wound closure consequent to SR. Findings are of practical importance for affected populations, since the potential for infection is heightened when the skin barrier is perturbed. Funding Sources: US Army MMRDC. Authors' views do not reflect official DoD or Army policy.